Two new species of Paraphilopterus Mey, 2004 (Phthiraptera: Ischnocera: Philopteridae) from New Guinean bowerbirds (Passeriformes: Ptilonorhynchidae) and satinbirds (Passeriformes: Cnemophilidae) - Gustafsson, Daniel R.; Bush, Sarah E. (Zootaxa, 2014)
Two new species of Paraphilopterus Mey, 2004 are described and named. Paraphilopterus knutieae n. sp. is described from two subspecies of Macgregor's bowerbirds: Amblyornis macgregoriae nubicola Schodde & McKean, 1973 and A. m. kombok Schodde & McKean, 1973, and Sanford's bowerbird: Archboldia sanfordi (Mayr & Gilliard, 1950) (Ptilonorhynchidae). Paraphilopterus meyi n. sp. is described from two subspecies of crested satinbirds: Cnemophilus macgregorii macgregorii De Vis, 1890 and C. m. sanguineus Iredale, 1948 (Cnemophilidae). These new louse species represent the first records of the genus Paraphilopterus outside Australia, as well as from host families other than the Corcoracidae. The description of Paraphilopterus is revised and expanded based on the additional new species, including the first description of the male of this genus. Also, we provide a key to the species of Paraphilopterus.